VOLATILITAS HARGA BAWANG DI JAWA BARAT DENGAN METODE ARCH/GARCH - Ranti Pramushinta Kurnia; Abdullah Ahmad Dzikrullah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
Food commodities such as shallots and garlic are still a concern for the Indonesian people, this is because prices are not fixed and fluctuate for each period. It is these price fluctuations that cause high price volatility. An illustration of the magnitude of the risks that will be faced by economic actors in the future can be illustrated by the magnitude of price changes that indicate market fluctuations in a period of time. The model that can be used to analyze the nature of price volatility is Autoregressive Conditional Heteroscedasticity (ARCH) and Generalized Autoregressive Conditional Heteroscedasticity (GARCH). The purpose of this study was to determine the price volatility of shallots and garlic in West Java Province for the period January 2013 to December 2021. The results showed that retail prices for garlic were heteroscedastic, so the model that was more suitable was ARCH/GARCH. As for the commodity of shallots that are homoscedastic, the model that is carried out is only up to the ARIMA model analysis. The volatility model for garlic is the ARCH(1) model. The results of the model estimation show that garlic price volatility is quite high